Financial Fragilities in Latin America : The 1980s and 1990s - Weisbrod, Steven (Occasional Papers; Occasional Paper ;, 1995)
By reviewing the experiences of Latin American countries with the restructuring of their financial sectors since 1982, this paper derives lessons regarding the most effective ways to deal with banking difficulties in developing countries. It then discusses whether these lessons have been put into practice during the latest crisis. A sample of five countries - Argentina, Chile, Colombia, Mexico, and Peru - is used for this purpose.